Assessment of Nurses' Knowledge Regarding Breast Cancer at Primary Health Care Centers in Al-Sader District - Ammar A Okab (Diyala Journal of Medicine, 2019)
Background: Breast cancer is the most common, prevalent and diagnosed that affects women and the leading cause of death and disability worldwide and is a leading cause of morbidity and mortality among women.